2019
DOI: 10.1111/1468-4446.12644
|View full text |Cite
|
Sign up to set email alerts
|

Social network engagement and subjective well‐being: a life‐course perspective

Abstract: Social networking is a digital phenomenon embraced by billions worldwide. Use of online social platforms has the potential to generate a number of benefits including to well‐being from enhanced social connectedness and social capital accumulation, but is also associated with several negative behaviours and impacts. Employing a life‐course perspective, this paper explores social networking use and its relationship with measures of subjective well‐being. Large‐scale UK panel data from wave 3 (2011–12) and 6 (201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 72 publications
(156 reference statements)
5
37
0
1
Order By: Relevance
“…Using a qualitative research method and stimulating participants to reflect on their own experiences and feelings related to their leisure time consumptions, we found that smartphones are not only the digital extensions of young adults' bodies but are perceived as companions, enablers or separators. Our results confirm the findings of past studies [5,7,8,11,12], revealing that young adults' leisure time activities, experiences and forms are digitized and experienced in hybrid spaces [23]. In the theoretical background, we mentioned that being "offline" nowadays is almost reduced to being asleep.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Using a qualitative research method and stimulating participants to reflect on their own experiences and feelings related to their leisure time consumptions, we found that smartphones are not only the digital extensions of young adults' bodies but are perceived as companions, enablers or separators. Our results confirm the findings of past studies [5,7,8,11,12], revealing that young adults' leisure time activities, experiences and forms are digitized and experienced in hybrid spaces [23]. In the theoretical background, we mentioned that being "offline" nowadays is almost reduced to being asleep.…”
Section: Discussionsupporting
confidence: 89%
“…It is commonplace by now to say that information and communication technology (ICT) is present in every part of human life with its advantages and disadvantages [3,7]. The advantages brought about by smartphones, such as time and communication efficiency, the immediate availability of information, the possibility of information sharing, etc., are undeniable [8]. Recent research [9] shows that the recreational use of virtual realities, among others, helps to improve the well-being of young adults while under lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have found social media to have a beneficial (Verduyn et al, 2017), harmful (Reer et al, 2019), or negligible (Utz & Breuer, 2017) relationship with well-being. For youth and young adults, increased social media use has been found to have a positive impact on life satisfaction (Wheatley & Buglass, 2019), and Instagram in particular has been identified as benefiting overall well-being (Pittman & Reich, 2016). Conversely, Kross et al (2013) found that Facebook use predicted a decline in life satisfaction and affect in young adults.…”
Section: Social Mediamentioning
confidence: 99%
“…The rapid and vast adaptation of social media technologies has produced concern about the possible negative effects, but the association between social media use and decreased wellbeing measures appears to be rather weak (Appel et al, 2020;Kross et al, 2020). Accordingly, researchers have proposed that the outcomes of social media use depend on the way platforms are used, and that the negative outcomes are concentrated among those who experience excessive social media use (Kross et al, 2020;Wheatley & Buglass, 2019). Whereas an extensive body of research has focused either on cybercrime victimization or on problematic social media use, few studies have focused explicitly on the link between problematic use and victimization experiences (e.g., Craig et al, 2020;Longobardi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%